Short-duration male migration and women's autonomy - evidence from rural India - Pattnaik, Itishree (Gujarat Institute of Development Research, 2019)
Presented by Itishree Pattnaik (Gujarat Institute of Development Research), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.